Perbandingan suasana akademik pada program pertukaran pelajar UNS - UNY - Azis, Abdul; Mahendrati, Gilang; Azizah, Ika Nur; Utami, Rizki Cahya (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This study aims to explain and describe the atmosphere of the UNS - UNY student exchange program. Where student exchange is one of the Merdeka Learning Campus Merdeka programs. Merdeka Campus is one of the policies of the Minister of Education and Culture. Student exchanges are carried out in the PGSD UNS and PGSD UNY study programs. This research uses descriptive research with survey methods. Comparison of the academic atmosphere in the student exchange program at UNS and UNY in terms of various aspects, namely: The process of implementing learning at UNS and UNY, student activity, how to teach lecturers at UNS/ UNY during lectures on the student exchange program.